Medicinal and nutritional characteristics of pineapple in human health: A review - Lalhruaitluangi, Noel; Mandal, Debashis (Journal of Postharvest Technology, 2022)
Pineapple (Ananas comosus) is the third most important fruit in world production. The fruit is a source of balanced nutrients that provide the human body with valuable macro and micro-nutrients, including calcium, carbohydrates, vitamins, minerals, fiber, enzymes, and bioactive compounds that aid in the process of digestion and contribute to human health. Pineapple can be used as a supplementary nutritional fruit for good personal health. It possesses the biologically useful ingredient bromelain, which has demonstrated significant anti-inflammatory, antibiotic, anti-cancer, and anticoagulative properties. The multitude of potential uses of bromelain, combined with the effects of many other nutrients found in pineapple, allows us to appreciate not only its unquestionable taste but also the other benefits of this fruit. Antioxidants in pineapples help fight against free radicals, preventing cancers, heart diseases, and lowering cholesterol levels. Pineapple has abundant health benefits and also has the potential for breakthroughs in the food industry and agriculture sector. The present review will focus on the developments and future scopes of the medicinal and nutritional properties of pineapple.